209k views
17 votes
Solve this please show your work <3

Solve this please show your work <3-example-1

1 Answer

9 votes

Given:

The expression is


\sqrt[3]{48}=\sqrt[3]{8\cdot \_\_}=

To find:

The simplified form of the expression.

Solution:

We have,


\sqrt[3]{48}=\sqrt[3]{8\cdot \_\_}=

The expression
\sqrt[3]{48} can be written as


\sqrt[3]{48}=\sqrt[3]{8\cdot 6}


\sqrt[3]{48}=\sqrt[3]{8}\cdot \sqrt[3]{6}
[\because \sqrt[3]{ab}=\sqrt[3]{a}\sqrt[3]{b}]


\sqrt[3]{48}=2\cdot \sqrt[3]{6}


\sqrt[3]{48}=2\sqrt[3]{6}

Therefore,
\sqrt[3]{48}=\sqrt[3]{8\cdot 6}=2\sqrt[3]{6}.

User Ttvd
by
5.4k points